2013
DOI: 10.1039/c3cp53796j
|View full text |Cite
|
Sign up to set email alerts
|

Subnanometer-sized Pt/Sn alloy cluster catalysts for the dehydrogenation of linear alkanes

Abstract: The reaction pathways for the dehydrogenation of ethane, propane, and butane, over Pt are analyzed using density functional theory (DFT). Pt nanoparticles are represented by a tetrahedral Pt 4 cluster. The objectives of this work were to establish which step is rate limiting and which one controls the selectivity for forming alkenes as opposed to causing further dehydrogenation of adsorbed alkenes to produce precursors responsible for catalyst deactivation due to coking. Further objectives of this work are to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 61 publications
5
61
0
Order By: Relevance
“…The Pt catalyst used in the PDH process is often impregnated with Sn as a co-catalyst [7][8][9][10][11]. Because the Pt-alkene interaction is stronger than the Pt-alkane interaction, unwanted side reactions such as hydrogenolysis and isomerization often occur [12].…”
Section: Introductionmentioning
confidence: 99%
“…The Pt catalyst used in the PDH process is often impregnated with Sn as a co-catalyst [7][8][9][10][11]. Because the Pt-alkene interaction is stronger than the Pt-alkane interaction, unwanted side reactions such as hydrogenolysis and isomerization often occur [12].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of a second metal, such as tin, indium, or gallium, to platinum has been found to be effective in increasing ethene selectivity and suppressing coke formation [6,[8][9][10][11]. Both geometric and electronic effects of the second metals have been proposed to explain their roles in modifying the catalyst surface and changing the surface chemistry involved in ethane dehydrogenation [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…While this aspect has been extensively investigated in terms of both experimental and theoretical methods, one concern is the issue of low alkene selectivity with respect to further dehydrogenation leading to the coking problem that the Pt catalysts suffered from in industry [17a,b] . To this end, Hauser et al reported that, with tetrahedral Pt 4 clusters, alkene desorption can be favored over further dehydrogenation of the adsorbed alkene when either H is absorbed on the cluster or substituting a Pt atom in the cluster with a Sn atom . This work provides good agreement with the superior selectivity and high atom efficiency when alloying Pt with Sn or adding hydrogen to the alkane feed…”
Section: Introductionmentioning
confidence: 59%